The Experience of Prospective Uhamka Teacher Students in Reconstructing Pedagogic Knowledge in DKI Jakarta - Nurafni,; Alyani, Fitri (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to obtain a picture experience of prospective teacher students in reconstructing their pedagogical knowledge when implementing field experience programs. The subjects in this study were prospective teacher students from the Mathematics Education Study Program with a total of five subjects. The research method used in this study is a Qualitative Descriptive, in which the researcher tries to reveal the data in depth to the research subject. Subject selection is based on Purposive Sampling technique where subjects are selected who have carried out field experience programs in the academic year 2017/2018, subject selection is also based on communication skills and willingness to be interviewed. The research procedures performed are reducing data, data exposure and drawing conclusions. The results of this study are all research subjects saying that two months is not enough time to provide pedagogical experience to prospective teacher students and the Field Experience Program is very useful in improving pedagogical understanding of prospective teacher students. One in five research subjects has pedagogical knowledge or experience from a course on campus. Two subjects have pedagogical experience from courses on campus and places of teaching (tutoring) and one subject has pedagogical experience from courses on campus and from internet media such as YouTube. All research subjects said that the supervisor did not play a role in providing pedagogical experience during the field experience program process, the field experience program Unit and School Staff also did not play a role in providing pedagogical experience during the field experience program, the field experience program unit was only as a mediator for the implementation of field experience program but it was different from the tutor teacher who had more roles in providing pedagogical experience during field experience program.